Validation of Semiempirical Calculation Methods for the Development of 1,2,3-Triazole-based Compounds - Ponco Iswanto; Yesicha Megawarni Lumban Raja; Zhafran Aliffathin; Ely Setiawan; Heny Ekowati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Compounds based on 1,2,3-triazole have been widely utilized as anticancer agents. There are hydrogen bonds in compounds that can interact with a target biomolecule to form new compounds or derivative compounds that have useful biological activities. The 1,2,3-triazole compound has proven biological activities, including analgesic, antimicrobial, antiviral, anti-inflammatory, and antifungal properties. Molecular modeling for the development of 1,2,3-triazole compounds can be performed using a computational chemistry approach. One of the calculation methods used in molecular modeling is semiempirical calculations. The semiempirical method consists of 12 methods. This research was conducted to select 1 of 12 methods for the 1,2,3-triazole compound. First, the research procedure was to optimize the 1,2,3-triazole compound. Second, calculated the NMR spectrum. Third, calculated the physical properties, such as bond length and bond angles, and then calculated the Predicted Residual Sum of Squares (PRESS) value. The research results showed that the INDO semiempirical method had the smallest (lowest) PRESS value, namely 1.679. The INDO semiempirical method was the most suitable method for calculating 1,2,3-triazole compounds.